PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP LOYALITAS KERJA KARYAWAN PADA PT. JASA RAHARJA CABANG PEKANBARU - Ridito, Rianopita; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conductedatthe PT Jasa Raharja Pekanbaru. The problem in this research is how toinfluencethe transformational leadership to loyalty working at the PT Jasa Raharja Pekanbaru. The purposeofthis research wastodetermine the effectof transformational leadership to loyalty working at the PT Jasa Raharja Pekanbaru.Qualitative data obtained from filling the questionnaire by respondents transformed into quantitative data to give a score to each answer choice Likert scale. The data analy